Multiply Nitrated High‐Energy Dense Oxidizers Derived from the Simple Amino Acid Glycine. Issue 46 (23rd September 2013) - Baumann, Andreas; Erbacher, Anna; Evangelisti, Camilla; Klapötke, Thomas M.; Krumm, Burkhard; Rest, Sebastian F.; Reynders, Martin; Sproll, Véronique
Abstract Various energetic polynitro esters, carbamates, and nitrocarbamates that were derived from the amino acid glycine were fully characterized by single‐crystal X‐ray diffraction, vibrational spectroscopy (IR and Raman), multinuclear NMR spectroscopy, elemental analysis, and differential scanning calorimetry (DSC). Owing to their positive oxygen balance, the suitability of these compounds as potential oxidizers in energetic formulations was investigated and discussed. In addition, the heats of formation of the products were calculated by using the Gaussian 09 program package at the CBS‐4M level of theory. From these values and the calculated densities (from the X‐ray data), several detonation parameters, such as detonation pressure, velocity, energy, and temperature, were computed by using the EXPLO5 code. Furthermore, their sensitivities towards impact, friction, and electrostatic discharge were tested by using a drop hammer, a friction tester (both BAM certified), and a small‐scale electrical‐discharge device, respectively.